Polyamide resin composition, molded article, and method for producing polyamide resin composition
A polyamide resin composition with defined VR, Mw/Mn, and Tcc-Tc, combined with inorganic reinforcement and carbon black, addresses the issue of strength and rigidity at high temperatures, providing improved tensile strength and creep resistance.
Patent Information
- Application Number
- JP2020074704
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2020-04-20
- Publication Date
- 2025-01-07
- Estimated Expiration
- 2040-04-20
AI Technical Summary
Existing polyamide resin materials lack sufficient strength and rigidity at high temperatures, particularly above 80°C, and exhibit poor creep resistance in weld parts.
A polyamide resin composition comprising specific conditions: formic acid relative viscosity (VR) of 30 to 50, Mw/Mn ratio of 2.0 to 2.5, and a crystallization temperature difference (Tcc-Tc) of 5°C to 10°C, along with inorganic reinforcing materials and a colorant like carbon black, enhances tensile strength and creep resistance.
The composition achieves good tensile strength and creep resistance at high temperatures, making it suitable for various applications.
Smart Images

Figure 0007609567000001 
Figure 0007609567000002 
Figure 0007609567000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a polyamide resin composition, a molded article, and a method for producing a polyamide resin composition. [Background technology]
[0002] 2. Description of the Related Art Polyamide resins have been widely used as materials for various parts in the fields of clothing, industrial materials, automobiles, electrical and electronic products, industrial applications, etc. because of their excellent moldability, mechanical properties, and chemical resistance.
[0003] In recent years, the environments in which polyamide resins are used have tended to be thermally and mechanically severe, and there is a demand for polyamide resin materials that have improved strength and rigidity under high temperature use and that experience little change in physical properties when used in such severe environments.
[0004] In order to meet the above-mentioned demands, a polyamide resin composition in which the Si element content and the Na element content in the glass fiber are specified has been disclosed as a method for improving the mechanical properties of polyamide resin materials (see, for example, Patent Document 1). [Prior art documents] [Patent documents]
[0005] [Patent Document 1] JP 2018-70830 A Summary of the Invention [Problem to be solved by the invention]
[0006] However, the polyamide resin materials proposed so far still have room for improvement in terms of strength and rigidity when used at high temperatures of about 80° C. or higher, and there is a demand for further improvements in the physical properties of polyamide resin materials.
[0007] The present invention has been made in consideration of the above circumstances, and provides a polyamide resin composition which, when molded into a molded product, has good tensile strength at high temperatures of about 80°C or higher and good creep resistance at welds. [Means for solving the problem]
[0008] That is, the present invention includes the following aspects. (1) A polyamide resin composition comprising (A) a polyamide resin, (B) an inorganic reinforcing material, and (C) a colorant, A polyamide resin composition satisfying the following conditions (a) to (c): (a) Formic acid relative viscosity VR is 30 or more and 50 or less; (b) the ratio Mw / Mn of the weight average molecular weight Mw to the number average molecular weight Mn is 2.0 or more and 2.5 or less; (c) When measured by differential scanning calorimetry, the difference Tcc-Tc between the crystallization onset temperature Tcc and the crystallization peak temperature Tc obtained when cooling at 100°C / min is 5°C or more and 10°C or less. (2) The polyamide resin composition according to (1), wherein the number average molecular weight Mn is 15,000 or more and 25,000 or less. (3) The polyamide resin composition according to (1) or (2), which has a storage modulus of 6000 MPa or more at 150° C. in a dry state as determined by dynamic viscoelasticity measurement. (4) The polyamide resin composition according to any one of (1) to (3), wherein the (A) polyamide resin has a crystallization enthalpy ΔHc of 60 J / g or more when cooled at 20° C. / min, as measured by differential scanning calorimetry. (5) The polyamide resin composition according to any one of (1) to (4), wherein the (A) polyamide resin is one or more polyamides selected from the group consisting of polyamide 66, polyamide 6, polyamide 6I, and copolymer polyamides consisting of two or more of these polyamides. (6) The polyamide resin composition according to any one of (1) to (5), wherein the content of the (B) inorganic reinforcing material is 10 parts by mass or more and 250 parts by mass or less per 100 parts by mass of the (A) polyamide resin. (7) The polyamide resin composition according to any one of (1) to (6), wherein the content of the colorant (C) is 0.005 parts by mass or more and 10 parts by mass or less relative to 100 parts by mass of the polyamide resin (A). (8) The polyamide resin composition according to any one of (1) to (7), wherein the colorant (C) is carbon black having an average primary particle diameter of 20 nm or less. (9) (D) further comprising a lubricant; The polyamide resin composition according to any one of (1) to (8), wherein the content of the (D) lubricant is 0.005 parts by mass or more and 3 parts by mass or less relative to 100 parts by mass of the (A) polyamide resin. (10) A molded article obtained by molding the polyamide resin composition according to any one of (1) to (9). (11) A method for producing the polyamide resin composition according to any one of (1) to (9), comprising the steps of: A production method comprising a step of melt-kneading the mixture of the (A) polyamide resin and the (C) colorant with the (B) inorganic reinforcing material in an extruder. Effect of the Invention
[0009] According to the polyamide resin composition and the method for producing the same of the above aspect, it is possible to provide a polyamide resin composition that, when molded into a molded article, has good tensile strength and good creep resistance at welds at high temperatures of about 80° C. or higher. The molded article of the above aspect is produced by molding the polyamide resin composition, and has good tensile strength and good creep resistance at welds at high temperatures of about 80° C. or higher. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0010] Hereinafter, an embodiment of the present invention (hereinafter simply referred to as "the present embodiment") will be described in detail. The following embodiments are merely illustrative for explaining the present invention, and are not intended to limit the present invention to the following contents. The present invention can be modified appropriately within the scope of the gist thereof.
[0011] <Polyamide resin composition> The polyamide resin composition of the present embodiment contains (A) a polyamide resin, (B) an inorganic reinforcing material, and (C) a colorant. The polyamide resin composition of the present embodiment satisfies the following conditions (a) to (c). (a) Formic acid relative viscosity VR is 30 or more and 50 or less; (b) the ratio Mw / Mn of the weight average molecular weight Mw to the number average molecular weight Mn is 2.0 or more and 2.5 or less; (c) When measured by differential scanning calorimetry, the difference Tcc-Tc between the crystallization onset temperature Tcc and the crystallization peak temperature Tc obtained when cooling at 100°C / min is 5°C or more and 10°C or less.
[0012] Regarding the above condition (a), the formic acid relative viscosity VR is 30 or more and 50 or less, preferably 32 or more and 45 or less, and more preferably 34 or more and 40 or less. By setting the VR to the above upper limit value or less, it is possible to ensure flowability and produce a thin-walled molded product. Furthermore, by setting the VR to the above lower limit value or more, it is possible to stabilize the metering time during molding and to prevent the resin from flowing out from the nozzle tip. Furthermore, it is possible to eliminate the causes of gas generation and mold deposits due to reduced thermal stability, and furthermore, it is possible to significantly improve the mechanical strength of the obtained molded product. The formic acid relative viscosity VR can be obtained, for example, by adding a polyamide resin composition to formic acid and comparing the viscosity of the soluble portion with the viscosity of formic acid itself. Specifically, it can be measured using the method described in the examples below.
[0013] Regarding the above condition (b), the ratio Mw / Mn of the weight average molecular weight Mw to the number average molecular weight Mn can be used as an index of the molecular weight distribution of the (A) polyamide resin. Mw / Mn is 2.0 or more and 2.5 or less, preferably 2.0 or more and 2.4 or less, and more preferably 2.0 or more and 2.3 or less. By making Mw / Mn equal to or less than the upper limit, the surface appearance of the polyamide resin composition is excellent. The weight average molecular weight Mw and number average molecular weight Mn of the polyamide resin composition can be measured, for example, by gel permeation chromatography (GPC). Specifically, they can be measured by the method shown in the examples described later. The weight average molecular weight Mw and number average molecular weight Mn of the polyamide resin composition are essentially obtained as the weight average molecular weight Mw and number average molecular weight Mn of the (A) polyamide resin. Examples of methods for controlling Mw / Mn within the above range include a method of adding a known polycondensation catalyst such as phosphoric acid or sodium hypophosphite as an additive during the hot melt polymerization of the (A) polyamide resin, and a method of controlling polymerization conditions such as heating conditions and reduced pressure conditions.
[0014] Regarding the above condition (c), the upper limit of the difference Tcc-Tc between the crystallization onset temperature Tcc and the crystallization peak temperature Tc obtained by differential scanning calorimetry when cooling at 100°C / min is 10°C, preferably 9°C, and more preferably 8°C. The lower limit of Tcc-Tc is 5°C. That is, Tcc-Tc is 5°C or more and 10°C or less, preferably 5°C or more and 9°C or less, and more preferably 5°C or more and 8°C or less. When Tcc-Tc is within the above range, the molded article has excellent strength.
[0015] The crystallization onset temperature Tcc and the crystallization peak temperature Tc can be measured, for example, by Diamond-DSC manufactured by PERKIN-ELMER. Specific measurement conditions include, for example, heating about 10 mg of a sample from 30° C. to 300° C. at a heating rate of 20° C. / min under a nitrogen atmosphere, then holding at 300° C. for 3 minutes, and then cooling from 300° C. to 30° C. at a cooling rate of 100° C. / min. The start temperature of the endothermic peak that appears at this time is the crystallization start temperature Tcc, and the temperature at the endothermic peak is the crystallization peak temperature Tc.
[0016] Methods for controlling Tcc-Tc within the above range include, for example, methods using carbon black or a nucleating agent, and a method using small particle diameter carbon black as the colorant (C) described below is particularly preferred.
[0017] The polyamide resin composition of the present embodiment has the above-mentioned configuration, and thus when molded into a molded article, it has excellent tensile strength at high temperatures of about 80° C. or higher and excellent creep resistance at welds.
[0018] Next, each component contained in the polyamide resin composition of the present embodiment will be described in detail below.
[0019] [(A) Polyamide resin] (A) Polyamide resin is a polymer having an amide bond (-NHCO-) in the main chain. (A) Polyamide resins include, but are not limited to, polyamide resins obtained by condensation polymerization of diamines and dicarboxylic acids, polyamide resins obtained by ring-opening polymerization of lactams, polyamide resins obtained by self-condensation of aminocarboxylic acids, and copolymers obtained by copolymerizing two or more types of monomers that constitute these polyamide resins. These polyamide resins may be used alone or in the form of a polyamide mixture of two or more kinds.
[0020] Examples of the polyamide resin (A) include polyamide 4 (poly-α-pyrrolidone), polyamide 6 (polycaproamide), polyamide 11 (polyundecane amide), polyamide 12 (polydodecanamide), polyamide 46 (polytetramethylene adipamide), polyamide 56 (polypentamethylene adipamide), polyamide 410 (polytetramethylene sebacamide), polyamide 412 (polytetramethylene dodecamide), polyamide 66 (polyhexamethylene diamipamide), polyamide 610 (polyhexamethylene sebacamide), polyamide 612 (polyheteroaryl amide), and the like. Polyamide 116 (polyundecamethylene adipamide), Polyamide 1010 (polydecamethylene sebacamide), Polyamide 1012 (polydecamethylene dodecamide), Polyamide 1210 (polydodecamethylene sebacamide), Polyamide 1212 (polydodecamethylene dodecamide), Polyamide TMHT (trimethylhexamethylene terephthalamide), Polyamide 6T (polyhexamethylene terephthalamide), Polyamide 2Me-5T (poly 2-methylpentamethylene terephthalamide (Me represents a methyl group; the same applies below).), Polyamide 9T (Polynonamethylene terephthalamide), 2Me-8T (Poly 2-methyloctamethylene terephthalamide), Polyamide 6I (Polyhexamethylene isophthalamide), Polyamide 6C (Polyhexamethylene cyclohexane dicarboxamide), Polyamide 2Me-5C (Poly 2-methylpentamethylene cyclohexane dicarboxamide), Polyamide 9C (Polynonamethylene cyclohexane dicarboxamide), 2Me-8C (Poly 2-methyloctamethylene cyclohexane dicarboxamide), Polyamide PACM12 (Polybis(4-aminocyclohexyl)methandodecamide ), polyamide dimethyl PACM12 (polybis(3-methyl-aminocyclohexyl)methandecamide), polyamide MXD6 (polymetaxylylene adipamide), polyamide 10T (polydecamethylene terephthalamide), polyamide 11T (polyundecamethylene terephthalamide), polyamide 12T (polydodecamethylene terephthalamide), polyamide 10C (polydecamethylene cyclohexane dicarboxamide), polyamide 11C (polyundecamethylene cyclohexane dicarboxamide), polyamide 12C (polydodecamethylene cyclohexane dicarboxamide), and the like. Among these, polyamide 6 (polycaproamide), polyamide 66 (polyhexamethylenediamipamide), polyamide 610 (polyhexamethylenesebacamide), polyamide 612 (polyhexamethylenedodecamide), polyamide 6T (polyhexamethyleneterephthalamide) or polyamide 6I (polyhexamethyleneisophthalamide) is preferred, and polyamide 6 (polycaproamide), polyamide 66 (polyhexamethylenediamipamide) or polyamide 6I (polyhexamethyleneisophthalamide) is more preferred.
[0021] The polyamide resin (A) may be a copolymerized polyamide obtained by copolymerizing each of the monomers constituting the polyamide resins exemplified above. When the polyamide resin (A) is a copolymerized polyamide, it may be a random copolymer or a block (graft) copolymer.
[0022] The content of the polyamide resin is, for example, preferably 30% by mass or more and less than 70% by mass, more preferably 35% by mass or more and 65% by mass or less, and even more preferably 40% by mass or more and 60% by mass or less, based on the total mass of the polyamide resin composition.
[0023] (A) Method for producing polyamide resin (1) Method for producing polymers and random copolymers Suitable examples of methods for producing polymers and random copolymers include the following production methods: The polymer referred to here means a polyamide obtained by polymerizing one kind of diamine and one kind of dicarboxylic acid, or one kind of lactam or aminocarboxylic acid.
[0024] When the (A) polyamide resin is a polymer or a random copolymer, the method for producing the polyamide resin is not particularly limited, but for example, the following methods 1) to 8) can be applied. 1) A method in which an aqueous solution or suspension of a dicarboxylic acid and a diamine, or a mixture of a dicarboxylic acid and a diamine salt with other components such as lactams and aminocarboxylic acids (hereinafter, these may be abbreviated as "the mixture") is heated and polymerized while maintaining the molten state (hereinafter, also referred to as "thermal melt polymerization method"); 2) A method in which an aqueous solution or suspension of a dicarboxylic acid and a diamine or a mixture thereof is heated and the precipitated prepolymer is removed (the "prepolymer method"); 3) A method of increasing the degree of polymerization of polyamide obtained by hot melt polymerization while maintaining the solid state at a temperature below the melting point ("hot melt polymerization-solid state polymerization method"); 4) A method in which an aqueous solution or suspension of a dicarboxylic acid and a diamine or a mixture thereof is heated, and the precipitated prepolymer is further melted again in an extruder such as a kneader to increase its degree of polymerization ("prepolymer-extrusion polymerization method"); 5) A method in which an aqueous solution or suspension of a dicarboxylic acid and a diamine or a mixture thereof is heated and the precipitated prepolymer is further maintained in a solid state at a temperature below the melting point of the polyamide to increase its degree of polymerization ("prepolymer-solid-state polymerization method"); 6) A method in which dicarboxylic acids and diamines or mixtures thereof are polymerized while remaining in the solid state ("monomer-solid-state polymerization method"); 7) A method of polymerizing a "salt of a dicarboxylic acid and a diamine" or a mixture thereof while maintaining the solid state ("salt-solid-phase polymerization method"); 8) A method of polymerization using a dicarboxylic acid halide and a diamine equivalent to the dicarboxylic acid (the "solution method"). Among the above-mentioned production methods, the thermal melt polymerization method is preferred from the viewpoint of productivity.
[0025] The polymerization form is not particularly limited, and may be a batch type or a continuous type. The polymerization apparatus is not particularly limited, and known apparatuses, for example, autoclave type reactors, tumbler type reactors, extruder type reactors such as kneaders, etc., can be used.
[0026] In the production of the (A) polyamide resin, when the monomers for the polyamide resin are polymerized, an end-capping agent can be further added for molecular weight adjustment. The end-capping agent is not particularly limited, and any known end-capping agent can be used.
[0027] Examples of the end-capping agent include, but are not limited to, monocarboxylic acids, monoamines, acid anhydrides such as phthalic anhydride, monoisocyanates, monoacid halides, monoesters, and monoalcohols. Among these, monocarboxylic acids and monoamines are preferred from the viewpoint of the thermal stability of the polyamide resin. These may be used alone or in combination of two or more.
[0028] Monocarboxylic acids that can be used as end-capping agents may be any that are reactive with amino groups, and include, but are not limited to, aliphatic monocarboxylic acids such as formic acid, acetic acid, propionic acid, butyric acid, valeric acid, caproic acid, caprylic acid, lauric acid, tridecylic acid, myristic acid, palmitic acid, stearic acid, pivalic acid, and isobutyric acid; alicyclic monocarboxylic acids such as cyclohexanecarboxylic acid; and aromatic monocarboxylic acids such as benzoic acid, toluic acid, α-naphthalenecarboxylic acid, β-naphthalenecarboxylic acid, methylnaphthalenecarboxylic acid, and phenylacetic acid. These may be used alone or in combination of two or more.
[0029] The monoamine that can be used as the end-capping agent may be any monoamine that is reactive with a carboxy group, and includes, but is not limited to, aliphatic monoamines such as methylamine, ethylamine, propylamine, butylamine, hexylamine, octylamine, decylamine, stearylamine, dimethylamine, diethylamine, dipropylamine, and dibutylamine; alicyclic monoamines such as cyclohexylamine and dicyclohexylamine; aromatic monoamines such as aniline, toluidine, diphenylamine, and naphthylamine; and the like. These may be used alone or in combination of two or more.
[0030] Examples of acid anhydrides that can be used as end-capping agents include, but are not limited to, phthalic anhydride, maleic anhydride, benzoic anhydride, acetic anhydride, and hexahydrophthalic anhydride. These may be used alone or in combination of two or more.
[0031] Examples of monoisocyanates that can be used as an end-capping agent include, but are not limited to, phenyl isocyanate, tolyl isocyanate, dimethylphenyl isocyanate, cyclohexyl isocyanate, butyl isocyanate, and naphthyl isocyanate. These may be used alone or in combination of two or more.
[0032] Examples of monoacid halides that can be used as end-capping agents include, but are not limited to, halogen-substituted monocarboxylic acids such as monocarboxylic acids such as benzoic acid, diphenylmethanecarboxylic acid, diphenylsulfonecarboxylic acid, diphenylsulfoxidecarboxylic acid, diphenylsulfidecarboxylic acid, diphenylethercarboxylic acid, benzophenonecarboxylic acid, biphenylcarboxylic acid, α-naphthalenecarboxylic acid, β-naphthalenecarboxylic acid, and anthracenecarboxylic acid. These may be used alone or in combination of two or more.
[0033] Examples of monoesters that can be used as end-capping agents include, but are not limited to, glycerin monopalmitate, glycerin monostearate, glycerin monobehenate, glycerin monomontanate, pentaerythritol monopalmitate, pentaerythritol monostearate, pentaerythritol monobehenate, pentaerythritol monomontanate, sorbitan monopalmitate, sorbitan monostearate, sorbitan monobehenate, sorbitan monomontanate, sorbitan dimontanate, sorbitan trimontanate, sorbitol monopalmitate, sorbitol monostearate, sorbitol monobehenate, sorbitol tribehenate, sorbitol monomontanate, and sorbitol dimontanate. These may be used alone or in combination of two or more.
[0034] Examples of monoalcohols that can be used as end-capping agents include, but are not limited to, propanol, butanol, pentanol, hexanol, heptanol, octanol, nonanol, decanol, undecanol, dodecanol, tridecanol, tetradecanol, pentadecanol, hexadecanol, heptadecanol, octadecanol, nonadecanol, eicosanol, docosanol, tricosanol, tetracosanol, hexacosanol, heptacosanol, octacosanol, triacontanol (all of which are linear and branched), oleyl alcohol, behenyl alcohol, phenol, cresol (o-, m-, p-isomer), biphenol (o-, m-, p-isomer), 1-naphthol, and 2-naphthol. These may be used alone or in combination of two or more.
[0035] (2) Method for producing block (graft) copolymer As a method for producing a block (graft) copolymer, the following production method can be mentioned as a suitable example.
[0036] When the polyamide resin (A) is a block (graft) copolymer, the block (graft) copolymer may be produced, for example, by appropriately combining two or more kinds of polyamide resins (A) and block copolymerizing them.
[0037] The (A) polyamide resin may be a copolymer polyamide containing two or more kinds of polyamides, or may be a combination of different copolymer polyamides.
[0038] The method of block (graft) copolymerization is not particularly limited, and various methods can be adopted, for example, as described below. For example, when at least two or more kinds of polyamides are melt-kneaded as raw materials, at least one selected from the group consisting of metal phosphite, phosphite ester compound, and molecular weight modifier is blended and melt-extruded to obtain a block copolymer. More specifically, the method described in Reference 1 (JP Patent Publication 2011-26396 A) can be adopted, and when at least two or more kinds of polyamide resins are used, the polyamide-polyamide exchange reaction is promoted.
[0039] In producing the block (graft) copolymer, for example, various kneading machines (such as a single-screw or multi-screw kneader, a kneader, a Henschel mixer, a ball mill, a planetary mill, a Banbury mixer, a roll, a Brabender plastogram, etc.) can be used. Among the above, the melt kneading method is preferred from the viewpoint of industrial cost. In the melt kneading, it is preferable to use a single screw extruder or a twin screw extruder, and it is more preferable to use a twin screw extruder.
[0040] (3) Method for producing polyamide mixture When the (A) polyamide resin is a polyamide mixture, the following production method can be mentioned as a method for producing the polyamide mixture. The polyamide mixture can be obtained by mixing two or more types of polyamides in appropriate combination.
[0041] The mixing method is not particularly limited, and various methods can be adopted, for example, as described below. For example, there is a method in which at least two or more kinds of polyamides (including copolymerized polyamides) are melt-kneaded as raw materials. For example, various kneading machines (such as a single-shaft or multi-shaft kneader, a kneader, a Henschel mixer, a ball mill, a planetary mill, a Banbury mixer, a roll, a Brabender plastogram, etc.) can be used. Among the above, the melt kneading method is preferred from the viewpoint of industrial cost. In the melt kneading, it is preferred to use a single screw extruder or a twin screw extruder, and it is more preferred to use a twin screw extruder.
[0042] (A) Physical properties of polyamide resin The crystallization enthalpy ΔHc of the (A) polyamide resin obtained by differential scanning calorimetry when cooled at 20° C. / min is preferably 60 J / g or more, more preferably 65 J / g or more, and even more preferably 70 J / g, from the viewpoints of heat resistance, low blocking property, and mold releasability. The upper limit of the crystallization enthalpy ΔHc of the (A) polyamide resin is not particularly limited, but is 100 J / g or less. The crystallization enthalpy ΔHc can be measured, for example, by Diamond-DSC manufactured by PERKIN-ELMER Co., Ltd. Specifically, it can be measured by the method shown in the examples described later.
[0043] [(B) Inorganic reinforcement] The (B) inorganic reinforcing material (hereinafter sometimes referred to as "reinforcing material", "(B) component", or "(B)") may be any material that improves at least one of the strength and rigidity of a material, and is not limited to the following. Specific examples of the (B) inorganic reinforcing material include glass fiber, carbon fiber, calcium silicate fiber, potassium titanate fiber, aluminum borate fiber, flaky glass, talc, kaolin, mica, hydrotalcite, calcium carbonate, zinc carbonate, zinc oxide, calcium hydrogen phosphate, wollastonite, silica, zeolite, alumina, boehmite, aluminum hydroxide, titanium oxide, silicon oxide, magnesium oxide, calcium silicate, sodium aluminosilicate, magnesium silicate, ketjen black, acetylene black, furnace black, carbon nanotubes, graphite, brass, copper, silver, aluminum, nickel, iron, calcium fluoride, mica, montmorillonite, swellable fluoromica, apatite, and the like. Among these, from the viewpoint of increasing strength and rigidity, glass fiber, carbon fiber, flaky glass, talc, kaolin, mica, calcium carbonate, calcium hydrogen phosphate, wollastonite, silica, carbon nanotubes, graphite, calcium fluoride, montmorillonite, expandable fluoromica, and apatite are preferred. Also, glass fiber, carbon fiber, wollastonite, talc, mica, kaolin, or silicon nitride is more preferable. The above-mentioned (B) inorganic reinforcing material may be used alone or in combination of two or more kinds.
[0044] From the viewpoint of being able to impart excellent mechanical properties to the polyamide resin composition, the glass fibers and carbon fibers preferably have a number average fiber diameter of 3 μm or more and 30 μm or less, a weight average fiber length in the polyamide resin composition of 100 μm or more and 750 μm or less, and a ratio of the weight average fiber length to the number average fiber diameter (the value obtained by dividing the weight average fiber length by the number average fiber diameter, also referred to as the aspect ratio) of 10 or more and 100 or less.
[0045] Here, the number average fiber diameter and weight average fiber length of the inorganic reinforcing material (B) can be calculated, for example, by the method shown below. Specifically, first, the polyamide resin composition is placed in an electric furnace, and the organic matter contained therein is incinerated, and, for example, 100 or more (B) inorganic reinforcing materials are arbitrarily selected from the residue. Next, the 100 or more (B) inorganic reinforcing materials are observed with a scanning electron microscope (SEM) to measure the fiber diameter of each of these (B) inorganic reinforcing materials. Next, the total value of the fiber diameters is divided by the number of selected (B) inorganic reinforcing materials to measure the number average fiber diameter. In addition, the weight average fiber length is measured using an SEM photograph at a magnification of 1000 times. Next, the weight average fiber length can be obtained by dividing the total value of the fiber lengths by the weight of the selected (B) inorganic reinforcing materials.
[0046] From the viewpoint of reducing warpage of the plate-shaped molded product and improving heat resistance, toughness, low water absorption, and heat aging resistance, the aspect ratio is preferably 1.5 or more, more preferably 1.5 to 10.0, even more preferably 2.5 to 10.0, and particularly preferably 3.1 to 6.0. When the aspect ratio is within the above range, crushing can be more effectively prevented during processing such as mixing with other components, kneading, and molding, and the desired effects for the molded product can be more fully obtained.
[0047] The thickness of glass fibers or carbon fibers with an aspect ratio of 1.5 or more is not limited to the following, but it is preferable that the minor axis d1 of the fiber cross section is 0.5 μm or more and 25 μm or less, and the major axis d2 of the fiber cross section is 1.25 μm or more and 250 μm or less. When it is within the above range, the difficulty of spinning the fiber can be effectively avoided, and the strength of the molded product can be improved without reducing the contact area with the resin (polyamide). It is more preferable that the minor axis d1 is 3 μm or more and 25 μm or less, and the aspect ratio is greater than 3.
[0048] These glass fibers and carbon fibers with an aspect ratio of 1.5 or more can be manufactured by using the methods described in, for example, Reference 2 (JP Patent Publication No. 3-59019), Reference 3 (JP Patent Publication No. 4-13300), Reference 4 (JP Patent Publication No. 4-32775), etc. In particular, glass fibers manufactured using either an orifice plate having a number of orifices on the bottom surface, in which a convex edge surrounding the multiple orifice outlets and extending downward from the bottom surface is provided, or a nozzle tip for spinning modified cross section glass fibers having a nozzle tip with a single or multiple orifice holes and a multiple convex edge extending downward from the tip of the outer periphery are provided are preferred. These fibrous reinforcing materials may be used as they are as fiber strands as rovings, or may be further cut and used as chopped glass strands.
[0049] From the viewpoint of being able to impart excellent mechanical properties to the polyamide resin composition, it is preferable for the wollastonite to have a number average fiber diameter of 3 μm or more and 30 μm or less, a weight average fiber length in the polyamide resin composition of 10 μm or more and 500 μm or less, and an aspect ratio [(weight average fiber length) / (number average fiber diameter)] of 3 or more and 100 or less.
[0050] From the viewpoint of imparting excellent mechanical properties to the polyamide resin composition, talc, mica, kaolin and silicon nitride preferably have a number average fiber diameter of 0.1 μm or more and 3 μm or less.
[0051] The (B) inorganic reinforcing material may be surface-treated with a silane coupling agent or the like. Examples of the silane coupling agent include, but are not limited to, aminosilanes such as γ-aminopropyltriethoxysilane, γ-aminopropyltrimethoxysilane, and N-β-(aminoethyl)-γ-aminopropylmethyldimethoxysilane; mercaptosilanes such as γ-mercaptopropyltrimethoxysilane and γ-mercaptopropyltriethoxysilane; epoxysilanes; and vinylsilanes. As the silane coupling agent, aminosilanes are particularly preferred.
[0052] In addition, glass fibers and carbon fibers may further contain a sizing agent. Examples of sizing agents include, but are not limited to, copolymers containing, as constituent units, a carboxylic acid anhydride-containing unsaturated vinyl monomer and an unsaturated vinyl monomer other than the carboxylic acid anhydride-containing unsaturated vinyl monomer, epoxy compounds, polycarbodiimide compounds, polyurethane resins, homopolymers of acrylic acid, copolymers of acrylic acid and other copolymerizable monomers, and salts of these with primary, secondary, and tertiary amines. These sizing agents may be used alone or in combination of two or more. In particular, from the viewpoint of mechanical strength of the polyamide resin composition, a copolymer containing a carboxylic acid anhydride-containing unsaturated vinyl monomer and an unsaturated vinyl monomer other than the carboxylic acid anhydride-containing unsaturated vinyl monomer as constituent units, an epoxy compound, a polycarbodiimide compound and a polyurethane resin, or a combination thereof is preferred, and a copolymer containing a carboxylic acid anhydride-containing unsaturated vinyl monomer and an unsaturated vinyl monomer other than the carboxylic acid anhydride-containing unsaturated vinyl monomer as constituent units, a polycarbodiimide compound and a polyurethane resin, or a combination thereof is more preferred.
[0053] Examples of the carboxylic acid anhydride-containing unsaturated vinyl monomer constituting the copolymer containing, as a constituent unit, a carboxylic acid anhydride-containing unsaturated vinyl monomer and an unsaturated vinyl monomer other than the carboxylic acid anhydride-containing unsaturated vinyl monomer include, but are not limited to, maleic anhydride, itaconic anhydride, and citraconic anhydride, and among these, maleic anhydride is preferred. On the other hand, the unsaturated vinyl monomer other than the carboxylic anhydride-containing unsaturated vinyl monomer refers to an unsaturated vinyl monomer different from the carboxylic anhydride-containing unsaturated vinyl monomer.Specific examples of the unsaturated vinyl monomer other than the carboxylic anhydride-containing unsaturated vinyl monomer include, but are not limited to, styrene, α-methylstyrene, ethylene, propylene, butadiene, isoprene, chloroprene, 2,3-dichlorobutadiene, 1,3-pentadiene, cyclooctadiene, methyl methacrylate, methyl acrylate, ethyl acrylate, ethyl methacrylate, etc.Among these, styrene or butadiene is preferred.
[0054] Among these material combinations as a bundling agent, one or more selected from the group consisting of a copolymer of maleic anhydride and butadiene, a copolymer of maleic anhydride and ethylene, a copolymer of maleic anhydride and styrene, and mixtures thereof are more preferable.
[0055] From the viewpoint of improving the fluidity of the polyamide resin composition, the copolymer containing the carboxylic acid anhydride-containing unsaturated vinyl monomer and the unsaturated vinyl monomer other than the carboxylic acid anhydride-containing unsaturated vinyl monomer as constituent units preferably has a weight average molecular weight of 2,000 or more, more preferably 2,000 to 1,000,000, and even more preferably 2,000 to 1,000,000. The weight average molecular weight can be measured by GPC.
[0056] Examples of epoxy compounds include, but are not limited to, aliphatic epoxy compounds such as ethylene oxide, propylene oxide, butene oxide, pentene oxide, hexene oxide, heptene oxide, octene oxide, nonene oxide, decene oxide, undecene oxide, dodecene oxide, pentadecene oxide, and eicosene oxide; glycidol, epoxypentanol, 1-chloro-3,4-epoxybutane, 1-chloro-2-methyl-3,4-epoxybutane, 1-chloro-2-methyl-3,4-epoxybutane, and 1-chloro-2-methyl-3,4-epoxybutane. Alicyclic epoxy compounds such as 4-dichloro-2,3-epoxybutane, cyclopentene oxide, cyclohexene oxide, cycloheptene oxide, cyclooctene oxide, methylcyclohexene oxide, vinylcyclohexene oxide, epoxidized cyclohexene methyl alcohol, etc.; terpene epoxy compounds such as pinene oxide, etc.; aromatic epoxy compounds such as styrene oxide, p-chlorostyrene oxide, m-chlorostyrene oxide, etc.; epoxidized soybean oil, epoxidized linseed oil, etc.
[0057] Polycarbodiimide compounds can be obtained by condensing compounds containing one or more carbodiimide groups (-N=C=N-).
[0058] The condensation degree of the polycarbodiimide compound is preferably from 1 to 20, and more preferably from 1 to 10. When the condensation degree of the polycarbodiimide compound is within the above range, a better aqueous solution or aqueous dispersion of the sizing agent can be obtained.
[0059] The polycarbodiimide compound is preferably a polycarbodiimide compound partially having a polyol segment. By having a polyol segment, the polycarbodiimide compound is easily made water-soluble, making it more suitable for use as a bundling agent for glass fibers or carbon fibers.
[0060] These polycarbodiimide compounds can be obtained by decarboxylating a diisocyanate compound in the presence of a known carbodiimide catalyst such as 3-methyl-1-phenyl-3-phospholene-1-oxide. As the diisocyanate compound, aromatic diisocyanates, aliphatic diisocyanates, alicyclic diisocyanates, and mixtures thereof can be used. Examples of diisocyanate compounds include, but are not limited to, 1,5-naphthalene diisocyanate, 4,4'-diphenylmethane diisocyanate, 4,4'-diphenyldimethylmethane diisocyanate, 1,3-phenylene diisocyanate, 1,4-phenylene diisocyanate, 2,4-tolylene diisocyanate, 2,6-tolylene diisocyanate, a mixture of 2,4-tolylene diisocyanate and 2,6-tolylene diisocyanate, hexamethylene diisocyanate, cyclohexane-1,4-diisocyanate, xylylene diisocyanate, isophorone diisocyanate, dicyclohexylmethane-4,4'-diisocyanate, methylcyclohexane diisocyanate, tetramethylxylylene diisocyanate, 2,6-diisopropylphenyl isocyanate, and 1,3,5-triisopropylbenzene-2,4-diisocyanate. By converting these diisocyanate compounds into carbodiimids, polycarbodiimide compounds having two isocyanate groups at their terminals can be obtained. Among these, dicyclohexylmethanecarbodiimide is preferably used from the viewpoint of improving reactivity.
[0061] A polycarbodiimide compound having one isocyanate group at its terminal can be obtained by, for example, further carbodiimidizing an equimolar amount of a monoisocyanate compound with a polycarbodiimide compound having two isocyanate groups at its terminals, or by reacting an equimolar amount of a polyalkylene glycol monoalkyl ether with the compound to form a urethane bond. Examples of the monoisocyanate compound include, but are not limited to, hexyl isocyanate, phenyl isocyanate, and cyclohexyl isocyanate. Examples of polyalkylene glycol monoalkyl ethers include, but are not limited to, polyethylene glycol monomethyl ether, polyethylene glycol monoethyl ether, and the like.
[0062] The polyurethane resin is not particularly limited as long as it is one that is commonly used as a bundling agent. For example, those synthesized from an isocyanate such as m-xylylene diisocyanate (XDI), 4,4'-methylenebis(cyclohexylisocyanate) (HMDI), or isophorone diisocyanate (IPDI) and a polyester- or polyether-based diol can be suitably used.
[0063] The homopolymer of acrylic acid (polyacrylic acid) preferably has a weight average molecular weight of 1,000 or more and 90,000 or less, and more preferably 1,000 or more and 25,000 or less.
[0064] The monomers forming a copolymer with acrylic acid that constitute the copolymer of acrylic acid and other copolymerizable monomers include, but are not limited to, monomers having at least one functional group selected from the group consisting of hydroxyl groups and carboxyl groups, and more specifically, one or more selected from the group consisting of acrylic acid, maleic acid, methacrylic acid, vinylacetic acid, crotonic acid, isocrotonic acid, fumaric acid, itaconic acid, citraconic acid, and mesaconic acid (excluding the case of only acrylic acid). It is preferable that the other copolymerizable monomers have one or more ester monomers among the above monomers.
[0065] The polymers of acrylic acid (including both homopolymers and copolymers) may be in the form of a salt. Salts of polymers of acrylic acid include, but are not limited to, primary, secondary, and tertiary amine salts. Salts of polymers of acrylic acid include, but are not limited to, triethylamine salts, triethanolamine salts, and glycine salts. From the viewpoints of improving the stability of a mixed solution with other concomitant chemicals (such as a silane coupling agent) and reducing the amine odor, the degree of neutralization is preferably 20% or more and 90% or less, and more preferably 40% or more and 60% or less.
[0066] The weight average molecular weight of the acrylic acid polymer that forms the salt is not particularly limited, but is preferably 3,000 or more from the viewpoint of improving the bundling property of glass fibers or carbon fibers, and is preferably 50,000 or less from the viewpoint of improving the mechanical properties when made into a polyamide resin composition. That is, the weight average molecular weight of the acrylic acid polymer that forms the salt is preferably 3,000 or more and 50,000 or less.
[0067] The glass fibers or carbon fibers containing a sizing agent can be obtained by applying the above-mentioned sizing agent to glass fibers or carbon fibers using a known method such as a roller-type applicator in a known glass fiber or carbon fiber production process to produce a fiber strand, which is then dried and reacted continuously. The fiber strands may be used as glass fibers or carbon fibers as rovings, or may be further cut into chopped strands for use. From the viewpoint of maintaining the bundling of the glass fibers or carbon fibers with respect to 100% by mass of the glass fibers or carbon fibers, the amount of the bundling agent added is preferably 0.2% by mass or more, more preferably 0.3% by mass or more, in terms of solid content, with respect to 100% by mass of the glass fibers or carbon fibers. On the other hand, from the viewpoint of improving the thermal stability of the polyamide resin composition, it is preferably 3% by mass or less, more preferably 2% by mass or less. That is, it is preferable to add (add) an amount equivalent to 0.2% by mass or more and 3% by mass or less, more preferably 0.3% by mass or more and 2% by mass or less, in terms of solid content. The strands may be dried after the cutting step, or may be cut after drying.
[0068] The content of the (B) inorganic reinforcing material is preferably 10 parts by mass or more and 250 parts by mass or less, more preferably 20 parts by mass or more and 150 parts by mass or less, even more preferably 25 parts by mass or more and 140 parts by mass or less, and particularly preferably 30 parts by mass or more and 120 parts by mass or less, relative to 100 parts by mass of the (A) polyamide resin. When the content of the (B) inorganic reinforcing material is equal to or more than the above lower limit, the effect of improving the strength of the molded product can be more sufficiently obtained, while when the content is equal to or less than the above upper limit, better manufacturability can be obtained in the extrusion step during the production of the polyamide resin composition.
[0069] In addition, when (A) polyamide resin and (B) inorganic reinforcing material are melt-kneaded, generally, (A) polyamide resin and (B) inorganic reinforcing material generate heat due to shear, and the resin temperature tends to rise. The higher the content of (B) inorganic reinforcing material, the higher the amount of heat generated by shear and the further the resin temperature tends to rise, and (A) polyamide resin tends to gel as the resin temperature rises. The gelation increases the melt viscosity and reduces the fluidity during molding, which tends to deteriorate the surface appearance. However, in the polyamide resin composition of the present embodiment, since the polyamide resin (A) satisfies the above-mentioned conditions (a) to (c), even when 250 parts by mass of the inorganic reinforcing material (B) is contained per 100 parts by mass of the polyamide resin (A), gelation due to an increase in resin temperature during melt-kneading can be suppressed, and a molded article with a good surface appearance can be obtained.
[0070] [(C) Colorant] (C) Colorants include, but are not limited to, dyes such as nigrosine; pigments such as titanium oxide and carbon black; metal particles such as aluminum, colored aluminum, nickel, tin, copper, gold, silver, platinum, iron oxide, stainless steel, and titanium; and metallic pigments such as mica pearl pigments, colored graphite, colored glass fibers, and colored glass flakes. Among these, it is preferable that the colorant (C) contains carbon black.
[0071] The average primary particle size of carbon black is preferably 10 nm or more and 40 nm or less, more preferably 10 nm or more and 30 nm or less, and even more preferably 10 nm or more and 20 nm or less. When the average primary particle size is equal to or more than the lower limit, the dispersibility in the composition can be improved, and when the average primary particle size is equal to or less than the upper limit, the strength and rigidity of the molded article can be more effectively expressed. In addition, when the average primary particle size is 20 nm or less, the tensile strength at a high temperature of about 80° C. or more and the creep resistance property at the weld part can be particularly good when the molded article is made. The average primary particle size herein means the average value calculated by obtaining a magnified image of an aggregate according to the procedure described in the ASTM D3849 standard (Standard Test Method for Carbon Black - Morphological Characterization by Electron Microscopy), measuring the particle sizes of 3,000 unit constituent particles from this aggregate image. In addition, carbon black with a specific surface area of 50 m 2 / g or more 300m 2 / g or less (BET adsorption method) and an oil absorption amount (measured using dibutyl phthalate) of 50 mL / 100 g or more and 150 mL / 100 g or less can be preferably used.
[0072] Nigrosine is not particularly limited, but examples thereof include black azine-based condensation mixtures such as triphenazine oxazine and phenazine azine, which are described in COLORINDE X as CISOLVENT BLACK 5 and CISOLVENT BLACK 7. In addition, it does not matter if they are partially modified. Examples of commercially available nigrosine include Nubian Black PA-9801, Nubian Black PA-9800, and Nubian Black PA-0800.
[0073] The content of the (C) colorant is preferably 0.005 parts by mass or more and 10 parts by mass or less, more preferably 0.02 parts by mass or more and 0.1 parts by mass or less, still more preferably 0.025 parts by mass or more and 0.1 parts by mass or less, and particularly preferably 0.03 parts by mass or more and 0.06 parts by mass or less, relative to 100 parts by mass of the (A) polyamide resin. Furthermore, in the case where the colorant (C) is carbon black, the content of the carbon black is preferably 0.02 parts by mass or more and 0.1 parts by mass or less, more preferably 0.025 parts by mass or more and 0.1 parts by mass or less, and even more preferably 0.03 parts by mass or more and 0.06 parts by mass or less, relative to 100 parts by mass of the polyamide resin (A).
[0074] [(D) Lubricant] The polyamide resin composition of the present embodiment may further contain (D) a lubricant.
[0075] (D) Lubricants are any lubricants that improve the plasticization and releasability during molding, but are not limited to the following, and examples thereof include higher fatty acids, higher fatty acid metal salts, higher fatty acid esters, higher fatty acid amides, waxes, polyhydric alcohols, and the like.
[0076] Examples of higher fatty acids include, but are not limited to, saturated or unsaturated, linear or branched aliphatic monocarboxylic acids having 8 to 40 carbon atoms, such as stearic acid, palmitic acid, behenic acid, erucic acid, oleic acid, lauric acid, montanic acid, etc. Among these, stearic acid or montanic acid is preferred from the viewpoints of suppressing gas generation during melt processing and suppressing mold deposits on a mold during molding.
[0077] The higher fatty acid metal salt is a metal salt of a higher fatty acid. The metal element constituting the metal salt is preferably an element of Group 1, 2 or 3 of the periodic table, zinc, or aluminum, and more preferably calcium, sodium, potassium, or magnesium. Specific examples of higher fatty acid metal salts include, but are not limited to, calcium stearate, aluminum stearate, zinc stearate, magnesium stearate, calcium montanate, sodium montanate, calcium palmitate, etc. Among these, metal salts of montanic acid or metal salts of stearic acid are preferred from the viewpoints of suppressing gas generation during melt processing and suppressing mold deposits on a mold during molding.
[0078] The higher fatty acid ester is an ester of a higher fatty acid and an alcohol. Among these, from the viewpoints of suppressing gas generation during melt processing and suppressing mold deposits on a mold during molding, esters of aliphatic carboxylic acids having 8 to 40 carbon atoms and aliphatic alcohols having 8 to 40 carbon atoms are preferred. Here, the higher fatty acids that can be used are those mentioned above. Examples of fatty alcohols include, but are not limited to, stearyl alcohol, behenyl alcohol, lauryl alcohol, and the like. Examples of higher fatty acid esters include, but are not limited to, stearyl stearate, behenyl behenate, and the like.
[0079] Higher fatty acid amides are amide compounds of higher fatty acids. Examples of higher fatty acid amides include, but are not limited to, stearic acid amide, oleic acid amide, erucic acid amide, ethylene bisstearylamide, ethylene bisoleylamide, N-stearylstearylamide, and N-stearylerucic acid amide. Among these, from the viewpoints of suppressing gas generation during melt processing and suppressing mold deposits on a mold during molding, stearic acid amide, erucic acid amide, ethylene bisstearylamide, and N-stearyl erucic acid amide are preferred, and ethylene bisstearylamide and N-stearyl erucic acid amide are more preferred.
[0080] Examples of the wax include montanic acid wax, polyethylene wax, polypropylene wax, and silicone wax.
[0081] Examples of polyhydric alcohols include pentaerythritol, dipentaerythritol, and tripentaerythritol.
[0082] The content of the (D) lubricant is preferably 0.005 parts by mass or more and 3 parts by mass or less, more preferably 0.01 parts by mass or more and 2 parts by mass or less, and even more preferably 0.05 parts by mass or more and 1 part by mass or less, per 100 parts by mass of the (A) polyamide resin. By making the content of the (D) lubricant equal to or more than the lower limit, the effect of improving the plasticization property and the mold releasability during molding can be more sufficiently obtained, while by making the content of the (D) lubricant equal to or less than the upper limit, better manufacturability can be obtained in the extrusion step during the production of the polyamide resin composition.
[0083] [(E) Heat stabilizer] The polyamide resin composition of the present embodiment may further contain (E) a heat stabilizer (hereinafter sometimes referred to as "heat stabilizer", "component (E)", or "(E)").
[0084] The (E) heat stabilizer may be any that suppresses thermal deterioration of the material, prevents discoloration when heated, and improves heat aging resistance and weather resistance. Examples of the heat stabilizer include, but are not limited to, copper-based stabilizers such as copper compounds such as copper acetate and copper iodide, phenol-based stabilizers such as hindered phenol compounds, phosphite-based stabilizers, hindered amine-based stabilizers, triazine-based stabilizers, and sulfur-based stabilizers. Further examples include the above-mentioned antioxidants such as alkylphenols, alkylene bisphenols, and alkylphenol thioethers, and ultraviolet absorbing agents such as salicylic acid esters, benzotriazoles, and hydroxybenzophenones.
[0085] The content of the (E) heat stabilizer is preferably 0.005 parts by mass or more and 10 parts by mass or less based on 100 parts by mass of the (A) polyamide resin. By making the content of the (E) heat stabilizer equal to or more than the above lower limit, the effect of improving the heat stability can be obtained more sufficiently, while by making the content of the (E) heat stabilizer equal to or less than the above upper limit, better manufacturability can be obtained in the extrusion step during the production of the polyamide resin composition.
[0086] [(F) Flame retardants] The polyamide resin composition of the present embodiment may further contain (F) a flame retardant (hereinafter sometimes referred to as "flame retardant", "(F) component", or "(F)").
[0087] (F) Flame retardants are those that improve flame retardancy, but are not limited to the following, and examples thereof include non-halogen flame retardants and halogen flame retardants.
[0088] As the (F) flame retardant, from the viewpoints of suppressing gas generation during melt processing and suppressing mold deposits on the mold during molding, non-halogen flame retardants or bromine flame retardants are preferred.
[0089] Examples of non-halogen flame retardants include, but are not limited to, phosphorus-based flame retardants such as red phosphorus, ammonium phosphate, and ammonium polyphosphate; hydrates of metal hydroxides or inorganic metal compounds such as aluminum hydroxide, magnesium hydroxide, dolomite, hydrotalcite, calcium hydroxide, barium hydroxide, basic magnesium carbonate, zirconium hydroxide, tin oxide, zinc stannate, and zinc hydroxystannate; inorganic compound-based flame retardants such as boric acid compounds such as zinc borate, zinc metaborate, and barium metaborate; triazine-based flame retardants such as melamine, melam, melem, and melon (a product of deammoniating three to three molecules of melem at 300° C. or higher), melamine cyanurate, melamine phosphate, melamine polyphosphate, succinoguanamine, adipoguanamine, methylglutaroguanamine, and melamine resin; and silicone-based flame retardants such as silicone resin, silicone oil, and silica.
[0090] Examples of brominated flame retardants include, but are not limited to, brominated polystyrene, brominated polyphenylene ether, brominated bisphenol type epoxy polymer, brominated crosslinked aromatic polymer, etc. Flame retardant assistants such as antimony trioxide can also be used in combination.
[0091] The content of the (F) flame retardant is preferably 1 part by mass or more and 30 parts by mass or less based on 100 parts by mass of the (A) polyamide resin. By making the content of the (F) flame retardant equal to or more than the lower limit, the effect of improving flame retardancy can be more sufficiently obtained. On the other hand, by making the content equal to or less than the upper limit, better manufacturability can be obtained in the extrusion step during the production of the polyamide resin composition, and a large decrease in mechanical properties when the molded product is produced can be more suppressed.
[0092] [(G) Other ingredients] The polyamide resin composition of the present embodiment may contain other components (G) other than the above-mentioned components (A) to (F) as necessary, within the scope of not impairing the object of the present embodiment. Examples of the (G) other components include other polymers and ordinary additives used in the (A) polyamide resin, such as a crystal nucleating agent.
[0093] Examples of other polymers include, but are not limited to, polyethylene, polypropylene, polystyrene, ABS resin, polyacetal, polyethylene terephthalate, polybutylene terephthalate, polyamide, polycarbonate, (modified) polyphenylene ether, polyphenylene sulfide, cycloolefin polymer, liquid crystal polyester, polyetherimide, polysulfone, polyethersulfone, polyamideimide, thermoplastic polyimide, polyetherketone, polyetheretherketone, fluororesin, polybenzimidazole, and the like.
[0094] Examples of the crystal nucleating agent include, but are not limited to, boron nitride and talc.
[0095] <Method of producing polyamide resin composition> The polyamide resin composition of the present embodiment is obtained by mixing (A) a polyamide resin, (B) an inorganic reinforcing material, (C) a colorant, and, if necessary, the above-mentioned components (D) to (G). The method for producing the polyamide resin composition of the present embodiment (hereinafter, simply referred to as the "production method of the present embodiment") is not particularly limited, and a conventionally known method can be applied.
[0096] Among these, the manufacturing method of the present embodiment is preferably a manufacturing method including a step of melt-kneading (A) a polyamide resin and (C) a colorant, and, if necessary, a mixture of the above components (D) to (G) and (B) an inorganic reinforcing material in an extruder.
[0097] The blending amount of each component when producing the polyamide resin composition of the present embodiment is the same as the content of each component in the polyamide resin composition described above.
[0098] The melt-kneading temperature is preferably about 1° C. to 100° C. higher than the melting point of the (A) polyamide resin, and more preferably about 10° C. to 50° C. higher than the melting point of the (A) polyamide resin.
[0099] <Characteristics of polyamide resin composition> The polyamide resin composition of the present embodiment preferably has a number average molecular weight Mn of 15,000 to 25,000, more preferably 16,000 to 24,000, and even more preferably 17,000 to 23,000. By having the number average molecular weight Mn within the above range, a polyamide composition having excellent mechanical properties, particularly hot rigidity, flowability, etc. can be obtained. In addition, a polyamide composition containing a component typified by an inorganic reinforcing material has excellent surface appearance. The number average molecular weight Mn can be used as an index of the molecular weight distribution of the (A) polyamide resin. The number average molecular weight Mn can be measured, for example, by using GPC. Specifically, it can be measured by using the method shown in the examples described later.
[0100] The polyamide resin composition of the present embodiment preferably has a storage modulus E' at 150°C in a dry state determined by dynamic viscoelasticity measurement of 6000 MPa or more, more preferably 7000 MPa or more, and even more preferably 8000 MPa or more. The upper limit of the storage modulus is not particularly limited, and the higher the better. The storage modulus E' in a dry state obtained by dynamic viscoelasticity measurement can be measured, for example, using an Epressor 150N manufactured by GABO under conditions of a frequency of 8 Hz and a heating rate of 3°C / min, although this is not limited to the following. Methods for controlling the storage modulus E' at 150°C of the polyamide resin composition of the present embodiment to the above lower limit include, for example, a method for controlling the molecular weight of (A) the polyamide resin, and a method for controlling the content of (B) the inorganic reinforcing material in the polyamide resin composition.
[0101] <Molded products> The molded article of the present embodiment is produced by molding the polyamide resin composition.
[0102] The molded article of the present embodiment can be produced by molding the polyamide resin composition by a known molding method, such as extrusion molding, injection molding, vacuum molding, blow molding, injection compression molding, decorative molding, other material molding, gas-assisted injection molding, foam injection molding, low-pressure molding, ultra-thin injection molding (ultra-high speed injection molding), in-mold composite molding (insert molding, outsert molding), etc.
[0103] The molded product of this embodiment has good tensile strength at high temperatures of about 80°C or higher and good creep resistance at welds, and can therefore be used in a wide range of applications, such as automotive parts, electrical parts, electronic parts, portable electronic device parts, machine and industrial parts, office equipment parts, and aviation and space parts. EXAMPLES
[0104] The present invention will be described in detail below with reference to specific examples, but the present invention is not limited to the following examples. The raw materials used and the methods for measuring and evaluating the physical properties are as follows.
[0105] <Raw materials> [(A) Polyamide resin] (A-1) Polyamide 66 Formic acid relative viscosity VR: 46 (A-2) Polyamide 66 Formic acid relative viscosity VR: 37 (A-3) Polyamide 6I Formic acid relative viscosity VR: 12 (A-4) Polyamide 6, manufactured by Ube Industries, product name SF1013A (Mw=31500, Mw / Mn=2.2) Formic acid relative viscosity VR: 45
[0106] Among the polyamide resins, the above (A-1) and (A-2) were produced according to Production Examples 1 to 3 described below.
[0107] [(B) Inorganic reinforcement] (B-1) Glass fiber (GF) Manufactured by Kyoseki Group Co., Ltd. Product name E7CS-10-568H (B-2) Glass fiber (GF) Manufactured by Kyoseki Group Co., Ltd. Product name E6CS-10-568H (B-3) Glass fiber (GF) Made by Nippon Electric Glass Co., Ltd. Product name ECS03 T-275H
[0108] [(C) Colorant] (C-1) Carbon black (primary particle size: 13 nm) (C-2) Carbon black (primary particle size: 27 nm) (C-3) Nigrosine, manufactured by Orient Chemical Industry Co., Ltd. Product name: Nubian Black TN-870
[0109] [(D) Lubricant] (D-1) "Struktol TR-063A" (product name) manufactured by Struktol of America (D-2) Dipentaerythritol: "Di-Penta90" (product name) manufactured by Perstorp Chemicals (D-3) Calcium stearate: acid value 0.02 mg KOH / g, free fatty acid 0.01 mass%
[0110] <Method of measuring physical properties> [Physical Properties 1] (Formic Acid Relative Viscosity VR) The formic acid relative viscosity VR was calculated by comparing the viscosity of a solution (soluble matter) prepared by adding the raw material (A) polyamide resin or the polyamide resin composition obtained in the Examples and Comparative Examples to formic acid with the viscosity of formic acid itself. Specifically, the measurement was carried out in accordance with ASTM-D789. More specifically, the viscosity was measured at 25°C using a solution in which the polyamide resin composition was dissolved to 8.4% by mass in a 90% by mass formic acid (10% by mass water) solution. The VR of the polyamide resin composition was obtained by subtracting the viscosity of the formic acid solution alone from the measured viscosity.
[0111] [Physical Properties 2] (Number average molecular weight Mn, weight average molecular weight Mw / number average molecular weight Mn) The number average molecular weight Mn and weight average molecular weight Mw of the polyamide resin compositions obtained in the Examples and Comparative Examples were measured using a GPC device (HLC-8020, manufactured by Tosoh Corporation) in terms of a PMMA (polymethyl methacrylate) standard sample (manufactured by Polymer Laboratory Co., Ltd.). 9.0 mg of the polyamide resin composition was dissolved in 3 mL of hexafluoroisopropanol (containing 0.005N sodium trifluoroacetate), and the solution obtained by filtering through a 0.45 μm filter was used as a measurement sample. The measurement conditions were as follows:
[0112] (Measurement conditions) Solvent: Hexafluoroisopropanol (0.005N sodium trifluoroacetate added) Flow rate: 0.5mL / min Sample injection volume: 0.1 mL Temperature: 30℃
[0113] The measured weight average molecular weight Mw was divided by the number average molecular weight Mn to calculate Mw / Mn.
[0114] [Physical Properties 3] (The difference between the crystallization onset temperature Tcc and the crystallization peak temperature Tc obtained by differential scanning calorimetry when cooling at 100°C / min., Tcc-Tc) The crystallization enthalpy of the polyamide resin compositions obtained in the Examples and Comparative Examples was measured in accordance with JIS-K7121 using a Diamond-DSC manufactured by PERKIN-ELMER Co., Ltd. The measurement was carried out under a nitrogen atmosphere. First, about 10 mg of the sample was heated from 30°C to 300°C at a heating rate of 20°C / min. Then, after keeping at 300°C for 3 minutes, it was cooled from 300°C to 30°C at a cooling rate of 100°C / min. The start temperature of the endothermic peak that appeared at this time was the crystallization start temperature Tcc, and the temperature at the endothermic peak was the crystallization peak temperature Tc. The crystallization peak temperature Tc was subtracted from the obtained crystallization start temperature Tcc to obtain the difference Tcc-Tc between the crystallization start temperature Tcc and the crystallization peak temperature Tc.
[0115] [Physical Properties 4] (Storage modulus at 150℃ when dry, determined from dynamic viscoelasticity measurements) Using a PS40E injection molding machine manufactured by Nissei Kogyo Co., Ltd., a molded article was molded according to JIS-K7139 under the injection molding conditions of a cylinder temperature of 290°C, a mold temperature of 80°C, injection for 10 seconds, and cooling for 10 seconds. The storage modulus of this molded article at 150°C was measured under the following conditions using a dynamic viscoelasticity evaluation device (EPLEXOR500N manufactured by GABO Co., Ltd.).
[0116] (Measurement conditions) Measurement mode: Tensile Measurement frequency: 8.00Hz Heating rate: 3℃ / min Temperature range: -100℃ to 250℃
[0117] [Physical Properties 5] (Crystallization enthalpy ΔHc obtained by differential scanning calorimetry when cooled at 20°C / min) (A) The crystallization enthalpy of the polyamide resin was measured in accordance with JIS-K7121 using a Diamond-DSC manufactured by PERKIN-ELMER Co., Ltd. The measurement was carried out under a nitrogen atmosphere. First, about 10 mg of the sample was heated from 30° C. to 300° C. at a heating rate of 20° C. / min. Then, after keeping at 300° C. for 3 minutes, it was cooled from 300° C. to 30° C. at a cooling rate of 20° C. / min. The exothermic peak that appeared at this time was taken as the crystallization peak, and the area of the crystallization peak was taken as the crystallization enthalpy ΔHc.
[0118] <Evaluation method> [Rating 1] (Tensile strength) A 4 mm thick dumbbell test piece was prepared according to the conditions specified in ISO294-1. Next, a tensile test was performed using the obtained test piece according to ISO527 at a tensile speed of 5 mm / min to measure the tensile strength in a high temperature environment of 80°C and 120°C. The test piece with the larger tensile strength (tensile strength of 170 MPa or more at 80°C; tensile strength of 130 MPa or more at 120°C) was evaluated as having excellent tensile strength.
[0119] [Rating 2] (Creep resistance at welds) In accordance with the conditions specified in ISO294-1, a dumbbell test piece with a thickness of 4 mm was prepared so that molten resin flowed into both ends of the dumbbell test piece in the longitudinal direction and a weld was formed in the center of the longitudinal direction. A load was applied to the obtained test piece in the range of 60% to 90% of the tensile breaking strength of the test piece in a 120°C atmosphere using a six-unit creep tester (model: 145-PC) manufactured by Yasuda Seiki Seisakusho. The measurement points that were tabulated for the time to break against the applied stress were logarithmically approximated to derive the stress value (MPa) at which the test piece breaks after 1000 hours of stress application. The larger stress value (stress value of 55 MPa or more) was evaluated as having excellent creep resistance.
[0120] <(A) Production of polyamide resin> [Production Example 1] (Production of Polyamide Resin A-1 (Polyamide 66)) The polymerization reaction of polyamide was carried out by the "thermal melt polymerization method" as follows. 1500g of an equimolar salt of adipic acid and hexamethylenediamine was dissolved in 1500g of distilled water to prepare a 50% by mass equimolar homogeneous aqueous solution of raw material monomers. This aqueous solution was charged into an autoclave with an internal volume of 5.4L and purged with nitrogen. The solution was concentrated by gradually removing steam to a solution concentration of 70% by mass while stirring at a temperature of 110°C to 150°C. The internal temperature was then raised to 220°C. At this time, the autoclave was pressurized to 1.8MPa. The reaction was continued for 1 hour while gradually removing steam to maintain the pressure at 1.8MPa until the internal temperature reached 245°C. Next, the pressure was reduced over 1 hour. After that, the inside of the autoclave was reduced to 650 torr using a vacuum device and maintained for 10 minutes. At this time, the final internal temperature of the polymerization was 265°C. Then, the mixture was pressurized with nitrogen, formed into a strand from the lower spinneret (nozzle), water-cooled, cut, and discharged in the form of pellets. The obtained pellets were dried at 100°C under a nitrogen atmosphere for 12 hours to obtain polyamide resin A-1. The Mw of polyamide resin A-1 was 40,000, and the Mw / Mn was 2.0.
[0121] [Production Example 2] (Production of Polyamide Resin A-2 (Polyamide 66)) Except for maintaining the inside of the autoclave at a reduced pressure of 650 torr for 20 minutes using a vacuum device, pellets of polyamide resin A-2 were obtained using the same method as that described in Production Example 1 ("melt polymerization method"). Polyamide resin A-2 had Mw of 35,000 and Mw / Mn of 2.0.
[0122] [Production Example 3] (Production of Polyamide Resin A-3 (Polyamide 6I)) The polymerization reaction of polyamide was carried out by the "thermal melt polymerization method" as follows. 1500 g of an equimolar salt of isophthalic acid and hexamethylenediamine and 1.5 mol % excess adipic acid based on the total equimolar salt components were dissolved in 1500 g of distilled water to prepare a 50 mass % equimolar homogeneous aqueous solution of the raw material monomers. While stirring at a temperature of 110°C to 150°C, the solution was concentrated by gradually releasing steam until the solution concentration reached 70% by mass. The internal temperature was then raised to 220°C. At this time, the autoclave was pressurized to 1.8 MPa. The reaction was continued for 1 hour while maintaining the pressure at 1.8 MPa by gradually releasing steam until the internal temperature reached 245°C. Next, the pressure was reduced over 30 minutes. After that, the inside of the autoclave was reduced to 650 torr using a vacuum device and maintained for 10 minutes. At this time, the final internal temperature of the polymerization was 265°C. The mixture was then pressurized with nitrogen to form a strand from the lower spinneret (nozzle), water-cooled, cut, and discharged in pellet form. The pellets were dried at 100°C under a nitrogen atmosphere for 12 hours to obtain polyamide resin A-3. The Mw of polyamide resin A-3 was 20,000, and the Mw / Mn was 2.0.
[0123] [Examples 1 to 15 and Comparative Examples 1 to 12] (Production of Polyamide Resin Compositions PA-a1 to PA-a15 and PA-b1 to PA-b5) Each polyamide resin composition was produced using (A) polyamide resin, (B) inorganic reinforcing material, (C) colorant, and (D) lubricant in the types and amounts shown in Tables 1 to 4. The (A) polyamide resin was dried under a nitrogen atmosphere to adjust the moisture content to about 0.2% by mass before being used as a raw material for the polyamide resin composition.
[0124] As the production apparatus for the polyamide resin composition, a twin-screw extruder (ZSK-26MC: manufactured by Coperion (Germany)) was used. The twin-screw extruder had an upstream supply port in the first barrel from the upstream side of the extruder, a downstream first supply port in the sixth barrel, and a downstream second supply port in the ninth barrel. In addition, the L / D ratio of the twin-screw extruder was 48, and the number of barrels was 12. In the twin-screw extruder, the temperature from the upstream supply port to the die was set to the melting point Tm2 of the polyamide resin (A) + 20°C, the screw rotation speed was set to 250 rpm, and the discharge rate was set to 25 kg / hour.
[0125] (A) polyamide resin, (C) colorant, and (D) lubricant, if necessary, were dry-blended, and then fed from an upstream feed port of a twin-screw extruder, and (B) inorganic reinforcing material was fed from a downstream first feed port of the twin-screw extruder, and melt-kneaded. The melt-kneaded product extruded from a die head was cooled in a strand shape, and pelletized to obtain pellets of a polyamide resin composition. The obtained pellets of the polyamide resin composition were dried in a nitrogen stream to reduce the water content in the polyamide resin composition to 500 ppm or less.
[0126] The polyamide resin compositions obtained in the Examples and Comparative Examples were measured for physical properties and evaluated using the above-mentioned methods. The results are shown in Tables 1 to 4.
[0127] [Table 1]
[0128] [Table 2]
[0129] [Table 3]
[0130] [Table 4]
[0131] As can be seen from Tables 1 to 4, the polyamide resin compositions PA-a1 to PA-a15 (Examples 1 to 15) contained (A) a polyamide resin, (B) an inorganic reinforcing material, and (C) a colorant, and had formic acid relative viscosity VR, ratio Mw / Mn of weight average molecular weight Mw to number average molecular weight Mn, and difference Tcc-Tc between crystallization onset temperature Tcc and crystallization peak temperature Tc obtained when cooled at 100°C / min within specific ranges as measured by differential scanning calorimetry, and had good tensile strength and creep resistance at welds at high temperatures of about 80°C or higher when molded into articles. In addition, in a comparison of polyamide resin compositions PA-a1 and PA-a2 (Examples 1 and 2) and PA-a9 and PA-a10 (Examples 9 and 10) containing different types of polyamide resin (A), the polyamide resin composition containing the polyamide resin (A) having a low relative formic acid viscosity tended to have better tensile strength and creep resistance at welds at high temperatures of about 80°C or higher when used as a molded product.
[0132] On the other hand, in the polyamide resin compositions PA-b1 to PA-b10 (Comparative Examples 1 to 10) in which Tcc-Tc was greater than 10°C, the molded products did not exhibit good tensile strength at high temperatures of about 80°C or higher and good creep resistance in the welds. In addition, the polyamide resin compositions PA-b11 to PA-b12 (Comparative Examples 11 to 12) having an Mw / Mn ratio of more than 2.5 were inferior in both tensile strength at high temperatures of about 80° C. or higher and creep resistance at welds when molded into articles. [Industrial Applicability]
[0133] According to the polyamide resin composition and the method for producing the same of this embodiment, it is possible to provide a polyamide resin composition that, when molded into a molded article, has good tensile strength and good creep resistance at welds at high temperatures of about 80° C. or higher. The molded article of this embodiment is made by molding the polyamide resin composition, and can be used in a wide range of applications, such as automobile parts, electric parts, electronic parts, portable electronic device parts, machine and industrial parts, office equipment parts, aviation and space parts, etc.
Claims
1. A polyamide resin composition comprising: (A) a polyamide resin; (B) an inorganic reinforcing material; and (C) a colorant, A polyamide resin composition satisfying the following conditions (a) to (c): (a) formic acid relative viscosity VR is 30 or more and 50 or less; (b) the ratio Mw / Mn of the weight average molecular weight Mw to the number average molecular weight Mn is 2.0 or more and 2.5 or less; (c) When measured by differential scanning calorimetry, the difference Tcc - Tc between the crystallization onset temperature Tcc and the crystallization peak temperature Tc obtained when cooling at 100°C / min is 5°C or more and 10°C or less.
2. The polyamide resin composition according to claim 1, wherein the number average molecular weight Mn is 15,000 or more and 25,000 or less.
3. 3. The polyamide resin composition according to claim 1, wherein the storage modulus at 150°C in a dry state determined by dynamic viscoelasticity measurement is 6000 MPa or more.
4. The polyamide resin composition according to any one of claims 1 to 3, wherein the polyamide resin (A) has a crystallization enthalpy ΔHc of 60 J / g or more when cooled at 20 ° C. / min by differential scanning calorimetry.
5. The polyamide resin composition according to any one of claims 1 to 4, wherein the polyamide resin (A) is one or more polyamides selected from the group consisting of polyamide 66, polyamide 6, polyamide 6I, and copolymerized polyamides consisting of two or more of these polyamides.
6. The polyamide resin composition according to any one of claims 1 to 5, wherein the content of the inorganic reinforcing material (B) is 10 parts by mass or more and 250 parts by mass or less relative to 100 parts by mass of the polyamide resin (A).
7. The polyamide resin composition according to any one of claims 1 to 6, wherein the content of the colorant (C) is 0.005 parts by mass or more and 10 parts by mass or less relative to 100 parts by mass of the polyamide resin (A).
8. The polyamide resin composition according to any one of claims 1 to 7, wherein the colorant (C) is carbon black having an average primary particle diameter of 20 nm or less.
9. (D) further comprising a lubricant; The polyamide resin composition according to any one of claims 1 to 8, wherein the content of the lubricant (D) is 0.005 parts by mass or more and 3 parts by mass or less relative to 100 parts by mass of the polyamide resin (A).
10. A molded article obtained by molding the polyamide resin composition according to any one of claims 1 to 9.
11. A method for producing the polyamide resin composition according to any one of claims 1 to 9, A production method comprising the step of melt-kneading the mixture of the (A) polyamide resin and the (C) colorant with the (B) inorganic reinforcing material in an extruder.
Citation Information
Patent Citations
Black polyamide resin composition
JP1997255869A
Polyamide resin composition excellent in weather resistance
JP2004107536A
Polyamide resin composition excellent in weatherability and method for producing the same
JP2011057977A
Polyamide resin composition and formed part
JP2015048424A
Polyamide resin composition and molding
JP2016124992A